The Influence of Mobile Application User Experience, Service Quality, and Social Interaction on Customer Satisfaction Quantitative Research in the Online Service Industry - Syamsuddin; Togatorop, Agus Leonard; Karubaba, Oktovianus Cristian; Sholahuddin, M. Zainal; Prasetya, Tri Budi (International Journal of Science and Society, 2024)
This research aims to investigate the influence of User Experience, Service Quality, and Social Interaction on Customer Satisfaction in the online service industry. Quantitative methods with multiple linear regression testing were used to analyze data from 100 respondents who used online services. The results show that Social Interaction has a significant influence on Customer Satisfaction, while User Experience and Service Quality are not significant individually. When these variables are combined, they collectively influence Customer Satisfaction positively. These findings highlight the importance of strengthening social interactions in online platforms to increase customer satisfaction. The practical implications of this research suggest companies should focus on developing adequate social interactions to enhance customer experience and ensure the success of online service strategies.